2016
DOI: 10.1515/pjvs-2016-0110
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Deficiency – new genetic defect transmitted to Polish Holstein-Friesian cattle

Abstract: The aim of the study was to find out whether carriers of new genetic defect Cholesterol Deficiency (CD) occur in the population of Polish Holstein-Friesian bulls. Twenty seven bulls were included in the analysis. Bulls were selected as having in the pedigree known carrier of CD (Maughlin Storm CANM000005457798). All bulls were diagnosed by the test described by Menzi et al. (2016) by using allele-specific PCR. Among 27 bulls, 9 new CD carriers were found. Our results show that causal mutation for CD is already… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Similar studies were carried out by other scientists, according to the results of genotyping of 27 servicing bulls of the Holstein-Friesian breed from Poland, and 9 heads were heterozygous carriers of the HCD haplotype (Kamiński & Ruść, 2016).…”
Section: Liter Ature Re Vie Wsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar studies were carried out by other scientists, according to the results of genotyping of 27 servicing bulls of the Holstein-Friesian breed from Poland, and 9 heads were heterozygous carriers of the HCD haplotype (Kamiński & Ruść, 2016).…”
Section: Liter Ature Re Vie Wsupporting
confidence: 71%
“…(2012). Meanwhile, in Poland, Kamiński and Ruść's study from 2016 found a higher prevalence of 33.3% among Polish bulls. In China, Zhang et al.…”
Section: Discussionmentioning
confidence: 93%
“…In another study in Germany, Schütz et al [22] found 12.5 % of carriers among HF bulls born between 2012 and 2015. Kamiñski and Ruoeae [12] reported a much higher CD carrier frequency (33.33 %) in Polish HFc. In Chinese HFc, a carrier prevalence of 5.07 and 1.11 % was found for bulls and cows, respectively [16].…”
Section: Resultsmentioning
confidence: 93%
“…Although molecular methods such as Polymerase Chain Reaction (PCR) and its variants are currently applied to diagnose the CD-causing mutation [5,12,17,22], there are no published studies in Uruguay on the application of these techniques for the accurate and effective detection of these transposable elements. The design of molecular diagnostic strategies for this mutation would be important for this Country, in order to achieve immediate results regarding the control of this disease, since Briano-Rodriguez et al [2] reported a prevalence of CD carriers of 2.61 % in a population sample of HF calves using the GeneSeek Genomic Profiler -GGP -Bovine 50K genotyping panel.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted by phenol method [18] from blood taken from tail vein. The primers used for PCR genotyping were 5´-GGTGACCATCCTCT-CTCTGC-3´ (the universal forward primer), 5´-AGTGGAACCCAGCTCCA-TTA-3´ (the revers primer for amplification of 249 bp fragment) to identify wild allele, and 5´-CACCTTCCGCTATTCGAGAG-3´ (the forward primer for 436 bp fragment) to identify mutant allele of APOB gene (indel-polymorphism) [19]. PCR protocol was as follows: 1 min at 95 С (initial denaturation); 30 s at 94 С, 30 s at 60 С, 30 s at 72 С (35 cycles); 10 min at 72 C (amplifier Thermal Cycler T1000, Bio-Rad Laboratories, Inc., USA).…”
Section: Introductionmentioning
confidence: 99%